Survival after Curative Treatment for Colon Cancer in Patients Younger than 50 Years of Age Showing a Different Outcome to the Prevailing Literature - Ibrahim H. Ozata (World Journal of Colorectal Surgery)
Background: Colorectal cancer is the third most common and second deadliest cancer globally. Increasingly, early-onset colorectal cancer is diagnosed in those under 50 years, leading to some countries advising screenings from ages 40 or 45 years. The ’position of the tumor, right or left, impacts the characteristics and prognosis of early-onset colorectal cancer.